Strengths and limitations of non-survey-based data sources for assessing adult vaccination coverage in the United States - Daley, Matthew F.; Homdayjanakul, Kamonthip J.; Hurley, Laura P.; Lu, Peng-Jun; Tsai, Yuping; Black, Carla L.; Patel, Suchita; Singleton, James A.; Crane, Lori A. (Expert review of vaccines, 2025)
Non-survey-based data sources (e.g. electronic health records, administrative claims) have been used to estimate vaccination coverage among US adults. However, these data sources were not collected for research or surveillance purposes and may have substantial limitations. The objectives of this narrative review were to: 1) identify published studies that used non-survey-based data sources to estimate adult vaccination coverage for one or more routinely recommended vaccines; and 2) summarize the strengths and limitations of these data sources for coverage assessments. Thirty-four publications derived from 9 data sources were reviewed: 16 publications were in a general population (i.e. defined by age), 12 were among pregnant women, and 6 were among individuals with chronic health conditions. While several data sources used continuous health insurance enrollment to define the study population, doing so limited generalizability to stably insured populations. Methods for obtaining race and ethnicity data were complex and potentially subject to bias. None of the reviewed studies presented any formal assessment of vaccine data validity. While multiple non-survey-based data sources have been used to assess adult vaccination coverage in the United States, important limitations exist, including related to generalizability, data validity, and risk of bias.